PEMULIAAN PINUS BOCOR GETAH: KORELASI GENETIK PRODUKSI GETAH PADA TIGA SUB GALUR UJI KETURUNAN PINUS MERKUSII DI KPH BANYUMAS BARAT - Gunawan Nugrahanto; Mohammad Na’iem; Sapto Indrioko; Eny Faridah; Widiyatno Widiyatno (Agrienvi: Jurnal Ilmu Pertanian, 2020)
This study aims to determine the genetic correlation of resin yield to growth (height, diameter and branch-free height) in three sub-lines of the progeny test Pinus merkusii. The research was conducted on the 11-year-old P. merkusii with high resin yield half-sib, using an Incomplete Block with a Row Column Design sub-line system, namely sub-lines (KBS Sumedang, KBS Jember, and East Java). The genetic correlation between resin yield with height, diameter and free-branch height generally has a relatively small value. The resin yield with diameter growth in the sub-line of KBS Jember has a positive correlation and is moderate (0.526), but this is different in the genetic correlation of resin yield with moderate branch-free height but negative (-0.498). In the sub-line of East Java, the correlation of resin yield characteristic with diameter growth was moderate but negative (-0.434). Further selection in the Jember KBS sub-line could be aimed at wood and resin yield, however for the Sumedang and East Java KBS sub-lines, further selection was only intended for resin yield. Key words: Genetic correlation, resin yield, Pinus merkusii, sub-line, progeny test